The relative contributions of obesity, vitamin D, leptin, and adiponectin to multiple sclerosis risk: A Mendelian randomization mediation analysis. (November 2021) - Harroud, Adil; Manousaki, Despoina; Butler-Laporte, Guillaume; Mitchell, Ruth E; Davey Smith, George; Richards, J Brent; Baranzini, Sergio E
Background: Obesity is associated with increased risk of multiple sclerosis (MS); however, the underlying mechanisms remain unclear. Objective: To determine the extent to which decreased vitamin D bioavailability and altered levels of adiponectin and leptin mediate the association between obesity and MS. Methods: We performed Mendelian randomization (MR) analyses to estimate the effects on MS of body mass index (BMI), 25-hydroxyvitamin D (25OHD), adiponectin, and leptin levels in a cohort of 14, 802 MS cases and 26, 703 controls. We then estimated the proportion of the effect of obesity on MS explained by these potential mediators. Results: Genetic predisposition to higher BMI was associated with increased MS risk (odds ratio (OR) = 1.33 per standard deviation (SD), 95% confidence interval (CI) = 1.09–1.63), while higher 25OHD levels reduced odds of MS (OR = 0.72 per SD, 95% CI = 0.60–0.87). In contrast, we observed no effect of adiponectin or leptin. In MR mediation analysis, 5.2% of the association between BMI and MS was attributed to obesity lowering 25OHD levels (95% CI = 0.3%–31.0%). Conclusions: This study found that a minority of the increased risk of MS conferred by obesity is mediated by lowered vitamin D levels, while leptin and adiponectin had no effect. Consequently, vitamin D supplementation would only modestly reverse the effect of obesity on MS.